Randomized clinical study on the influence of motivation and monitoring of health professionals in the breastfeeding practice (Research, Society and Development, 2021)
This study aimed to evaluate the impact of the intervention: motivation and follow-up by health professionals in the duration and exclusivity of breastfeeding, by means of a randomized clinical trial. In the pregnancy, women they were interviewed (n = 154) and followed up until the six month after delivery. In the pregnancy, all received pamphlets and watched a video on breastfeeding promotion in the first interview, being randomly divided into groups: intervention (n = 51) and control (n = 103). The group Intervention was receive home care for up to 5 days and a telephone call back 2 and 14 weeks after delivery by health professionals. After 6 months, 124 mothers (Intervention = 50 and Control = 74) were interviewed. The mothers' mean age was 26.5 (± 6.1) years, and the majority were non-white skin color (58.9%), lived with a partner (79%), with up to 8 years of schooling (70.2%); multiparous (64.5%); did not work (54.8%), and earned up to 2 Minimum Wages (81.4%). Most babies were male (52.4%) and born by cesarean section (61.3%). Exclusive breastfeeding rates in intervention were 84%, 82%, 54% and 34% for 5 days, 2 weeks, 14 weeks and 6 months, respectively and in control was 17.6% for 6 months. The group intervention had higher rates of exclusive breastfeeding (p = 0.03, RR 1.25) and breastfeeding (p = 0.02, RR 2.03) compared to control. The studied intervention (motivation and follow-up) promoted positive changes in the duration and exclusivity of breast feeding at 6 months of age, compared to traditional health education, and can be used in the promotion of breastfeeding practice by health services.